Late Pleistocene Emergence of Crystalline Canadian Shield Sources in Sediments of the Northern Gulf of Mexico. Issue 4 (26th April 2021) - Portier, Andrea M.; Thierens, Mieke; Martin, Ellen E.; Hemming, Sidney R.; Gombiner, Joel H.; Raymo, Maureen E.
Abstract: The regolith hypothesis attributes the inferred growth of a thicker and more voluminous Laurentide Ice Sheet (LIS) across the mid‐Pleistocene transition (MPT) to the removal of softer subglacial substrates of either regolith or sedimentary cover and subsequent exposure of crystalline bedrock with higher basal friction at the base of the LIS. This hypothesis predicts that sediment derived from the LIS was dominated by weathered sources prior to the MPT and then transitioned to fresh Canadian Shield sources during and after the MPT. Here, we present clay mineralogy, modified indices of chemical alteration, K/Ar ages and radiogenic isotopes (Sr, Nd, Pb) of Pleistocene clay detrital fractions from Ocean Drilling Program Site 625 in northeastern Gulf of Mexico to evaluate changes on glacial‐interglacial and longer‐term timescales in sediment composition during the Pleistocene and test this prediction. Mineralogical and geochemical proxies show a predominance of chemically weathered clays (kaolinite and smectite with clay ratios ≥3.0) sourced from the Appalachians as determined by radiogenic isotopes and K/Ar ages throughout the site's three million‐year sediment record. This is consistent with extensive pre‐Pleistocene weathering of Caledonian‐Appalachian (∼450 Ma) material that covered North American cratonic sources within the Mississippi drainage basin. However, following the MPT, we observe a unique addition of physically weathered clays (chlorite and illite with clay ratios <3.0) with radiogenic isotopes and K/Ar ages indicating contributions from more ancient geological sources, most simply explained as sediment derived from physical erosion from the crystalline Canadian Shield. These observations are generally consistent with predictions made by the regolith hypothesis. Plain Language Summary: During the mid‐Pleistocene Transition (MPT) approximately one million years ago, the volume of Northern Hemisphere ice sheets increased and the periodicity of glacial‐interglacial cycles shifted from 41‐kyr to 100‐kyr without an associated change in orbital forcing that drives these climate variations. A proposed explanation for this transition is the regolith hypothesis, which suggests erosion associated with repeated glaciations removed regolith (sediment) underlying the ice sheets and exposed crystalline bedrock. Increased friction between bedrock and base of the ice sheets limited ice slippage, leading to thicker, less responsive ice sheets. A testable prediction from this hypothesis is that material eroded by the ice sheet and transported to the Gulf of Mexico by the Mississippi River should be composed of chemically weathered sediments prior to the transition and mechanically weathered Canadian crystalline bedrock after the MPT. We tested this hypothesis by studying the geochemistry of early, mid, and late Pleistocene clay fractions in a deep‐sea core from the Gulf of Mexico. Our results indicate transport of chemically weathered regolith to the site throughout the Pleistocene and the addition of crystalline bedrock sources geochemically indicative of contributions from the Canadian Shield after the MPT. These findings are generally consistent with predictions associated with the regolith hypothesis. Key Points: Detrital fractions of early, mid, and late Pleistocene Ocean Drilling Program Site 625 samples are dominated by regolith sourced from Appalachian orogenies Late Pleistocene sediments in glacial intervals contain significant fresh crystalline material derived from the Canadian Shield Results consistent with regolith hypothesis that thicker ice sheets formed after softer cover eroded to expose crystalline Canadian Shield